(untitled) (Raparin Journal of Humanities (RJH), 2020)
This research is entitled (Using Etymology to Teach Second Language Words). It consists of an introduction and two main parts and conclusions. Overall, this research is about the method of etymology, how it plays an important role in teaching and learning second language words while learning the language in such a way that the word’s origin helps the learner to understand the verbal meaning sooner. And to guess the meaning of those words have the same roots. In this study, more of the English word was used, as many English words are available in the root language.. Finally, the results of this study are discussed.